2021
DOI: 10.1029/2020ja028742
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Latitude Whistler‐Mode and Higher‐Latitude Z‐Mode Emission at Jupiter Observed by Juno

Abstract: Whistler‐mode chorus emission is important in the scattering and acceleration of electrons and filling of the radiation belts at Jupiter. In this work whistler mode magnetic intensity levels at Jupiter are comprehensively binned and parameterized. The frequency range of whistler mode under study extends from the proton cyclotron frequency, fcH, to fceq/2, where fceq is the cyclotron frequency mapped to the magnetic equator. Parametric dependence of magnetic plasma wave intensity is obtained versus frequency, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(75 citation statements)
references
References 71 publications
(141 reference statements)
2
71
0
Order By: Relevance
“…Pitch angle scattering of the chorus emission is a gyroresonant interaction and is dependent on the parallel energy resonant condition. However, Menietti et al (2020) point out that Juno observations of whistler mode emission at magnetic latitudes   E 30° are likely to be auroral hiss emission from the Jovian polar regions with a larger range of wave normal angles than chorus emission, which has a source region near the magnetic equator, and a different free energy source. Reference to Figure 3 of Menietti et al (2020) demonstrates that Jovian auroral hiss can also be bursty in morphology.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Pitch angle scattering of the chorus emission is a gyroresonant interaction and is dependent on the parallel energy resonant condition. However, Menietti et al (2020) point out that Juno observations of whistler mode emission at magnetic latitudes   E 30° are likely to be auroral hiss emission from the Jovian polar regions with a larger range of wave normal angles than chorus emission, which has a source region near the magnetic equator, and a different free energy source. Reference to Figure 3 of Menietti et al (2020) demonstrates that Jovian auroral hiss can also be bursty in morphology.…”
Section: Introductionmentioning
confidence: 92%
“…In this study, we will focus on electron distributions that are measured over an energy range of about 25 eV->800 keV. Sampling time for the electrons is 0.5 s. Menietti et al (2020) ("previous survey") reported an initial low-latitude survey of whistler-mode emission observed by the Juno spacecraft during orbits 1-25, which orbited at a high inclination with a period of about 53 days. Juno's line of apsides precesses about one degree per orbit, moving the perijove latitude north from its initial location near the equator at the beginning of the mission.…”
Section: Jedimentioning
confidence: 99%
See 3 more Smart Citations